Characteristics of the gut microbiota and potential effects of probiotic supplements in individuals with type 2 diabetes mellitus - Maluhy, Rafael Ballan (2021)
With the advance of research related to the use of probiotics and prebiotics in human health in recent decades, their impact on the gut microbiota and their therapeutic effect on a variety of diseases has been explored. The composition of the gut microbiota varies between individuals and might be influenced by extrinsic (lifestyle, dietary pattern, geographic location) and intrinsic (age, genetics) factors, and its changes have been associated with metabolic diseases, inflammatory bowel diseases, neurological diseases, and other disorders. Among these diseases, type 2 diabetes mellitus (T2DM) stands out since it has a complex etiology and increasing prevalence worldwide. Current literature indicates that an imbalance in the intestinal microbial composition (dysbiosis) is associated with an increased risk for T2DM. The intestinal microbiota in individuals with T2DM is characterized by low diversity, reduction of short-chain fatty acid-producing bacteria, as well as in tryptophan metabolite-producing bacteria, in addition to an increase in the abundance of opportunistic pathogens, branched-chain amino acid-synthesizing bacteria (BCAA), and sulfate-metabolizing bacteria. Together, microbial metabolite production and bacterial components such as trimethylamine, BCAAs, imidazole propionate, and lipopolysaccharides trigger inflammatory responses that contribute to an increase in insulin resistance in this population. The use of probiotics aims to modulate the gut microbiota, increasing microbial diversity, reducing the production of harmful microbial metabolites, and reducing inflammatory processes, which may result in an improvement in metabolic and anthropometric parameters in T2DM. Despite the significant growth of publications on this topic, there are important controversies regarding the efficacy, safety, and mechanisms of action of probiotics. This dissertation aims to review the published bibliography, carry out a critical analysis of the literature, and, within the limitations of the published studies, elucidate and consolidate the scientific knowledge available so far.